Experimental study on metallic impurity behavior with boronization wall conditioning in EAST tokamak - Cheng, Yunxin (2024)
Operation of EAST tokamak with full metal wall without any wall conditioning are attempted in 2023 and 2024 experimental campaign to address the issues related to ITER tungsten wall operation. It is found that H-mode plasma could be sustained even with a substantial increase in metallic impurity content caused by strong plasmawall interaction under uncoated metal wall. Boronization wall conditioning is therefore performed to improve the plasma performance with higher injected power. This study aims to quantitatively assess the impact of boronization wall conditioning on metallic impurity concentration and behavior in the EAST tokamak. It is then proved to be an effective wall conditioning approach for significantly controlling high-Z impurity content. In this work, the impurity spectra at extreme ultraviolet (EUV) wavelength range measured by sets of fast-time-response and space-resolved EUV spectrometers are widely used in the data analysis. The variation in the boron content in plasma after boronization are investigated by monitoring the 2nd order of B V line at 48.59 Å. It is found that the persistence time of boron in EAST device after a boronization with 10 g of carborane (C2B10H12) is about 2000 s (~150 shots) of discharge duration. The impact of different wall conditions (uncoated metal wall and boron coated wall) on metallic impurity content are then quantitatively studied. After boronization, the concentration of tungsten (CW) and molybdenum (CMo) dropped by 85 %, e. g., from 2.0 × 10-4 to 4.1 × 10-5 and from 4.6 × 10- 5 to 6.3 × 10-6, respectively. While the concentration of copper (CCu) and iron (CFe) decreased by approximately 50 % and 65 %, respectively, e. g., from 4.3 × 10-5 to 2.1 × 10-5 and from 2.0 × 10-4 to 6.9 × 10-5. A comparison of the line emission profiles from tungsten ions of W26+ − W32+ and W43+ before and after boronization reveals an overall reduction in the intensity while without obvious change in the profile shape, which suggests a reduction in metallic impurities source after boronization instead of altering impurity transport in core plasma significantly.